Financial literacy and technological adoption on entrepreneur intention among youth in agriculture sector - Rashid, Intan Maizura Abdul; Faisal, Syahril Iman; Razak, Noraznira Abd; Zaini, Mohd Rasdi; Samah, Irza Hanie Abu (Journal of Asian Scientific Research, 2024)
This study examines the impact of financial literacy and technological adoption on entrepreneurial intentions among youth in agriculture sector. The study of entrepreneurial intention has been and will continue to be a topic of interest to academics because of its importance to the development of numerous nations. The literature on entrepreneurial intention has examined a wide range of issues, with a focus on the factors that influence entrepreneurial intention. Furthermore, technological advancements in agriculture could potentially resolve the issue of food security. The majority of these investigations in agriculture sector, though, were conducted elsewhere, for example, in Pakistan and Indonesia. The study’s focus on agriculture allowed them to examine the relationship between entrepreneurial intent and the sector. This study examines Malaysian youth’s desire to start their own businesses. It specifically aims to determine how technological adoption and financial literacy (financial attitude, financial behavior, and financial knowledge) affect entrepreneurial intention. A partial least squares–structural equation modeling (PLS-SEM) data analysis was carried out. The investigation employed purposive sampling. The results demonstrated that technological adoption and financial literacy (financial attitude, financial behavior, and financial knowledge) have a substantial impact on young people’s decision to become entrepreneurs. The findings of this study could contribute to the body of knowledge, and help policymakers create programs and policies. Future researchers can use this study to learn more about entrepreneurial intent in a financial context.